Promoting water awareness in university students through a game as a teaching strategy - Marlés-Betancourt, Claritza; Hermosa-Guzmán, Dennyse; Correa-Cruz, Lucelly (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The article proposes a didactic strategy through cooperative games to promote the water awareness of the student population of Business Administration, of the University of the Amazon, in the Colombian Amazon foothills. It is a research applied to the educational field with a descriptive, cross-sectional approach, which involves the phases of diagnosis, application and evaluation of the didactic intervention. The results show limitations of water environmental knowledge in the future professionals of the region, which constitute inputs for the design and construction of the cooperative game from the sociocultural perspective. The implementation reveals the potential of the game as a catalyst for learning, a motivator for changes in habits and practices regarding the rational use of water resources and the development of generic skills, such as: teamwork, assertive communication, consensus and decision decision making.